Challenges of developing, conducting, analysing and reporting a COVID-19 study as the COVID-19 pandemic unfolds: an online co-autoethnographic study - Roshan das Nair; Rachael Hunter; Nikos Evangelou; Afagh Garjani; Katherine A Tuite-Dalton; Rod M Middleton; Richard S Nicholas (BMJ Open)
Objectives To capture the complexities and unique experience of a newly formed multidisciplinary and multicentre research team developing and deploying a COVID-19 study and to identify lessons learnt.Design Co-autoethnographic study.Setting Staff at two UK academic institutions, a national charity and two major UK hospitals.Participants Researchers, clinicians, academics, statisticians and analysts, patient and public involvement representatives and national charity.Methods The sampling frame was any content discussed or shared between research team members (emails, meeting minutes, etc), standard observational dimensions and reflective interviews with team members. Data were thematically analysed.Results Data from 34 meetings and >50 emails between 17 March and 5 August 2020 were analysed. The analysis yielded seven themes with ‘Managing our stress’ as an overarching theme.Conclusions Mutual respect, flexibility and genuine belief that team members are doing the best they can under the circumstances are essential for completing a time-consuming study, requiring a rapid response during a pandemic. Acknowledging and managing stress and a shared purpose can moderate many barriers, such as the lack of face-to-face interactions, leading to effective team working.